A new clinical score for the prognosis of status epilepticus in adults. (14th July 2016) - González‐Cuevas, M.; Santamarina, E.; Toledo, M.; Quintana, M.; Sala, J.; Sueiras, M.; Guzman, L.; Salas‐Puig, J.
Abstract : Background and purpose: The severity of status epilepticus (SE) has an important impact in clinical outcomes. The Status Epilepticus Severity Score (STESS) is a score for predicting mortality in SE at admission. The baseline modified Rankin Scale (mRS) might be a prognostic factor for assessing the short‐tem outcomes of SE. Therefore, our aim was to evaluate the effectiveness of mRS and whether its addition to the STESS improves the prediction of mortality. Methods: Consecutive patients with SE and aged >16 years were recruited during 3 years. Receiver operating characteristic curves and a logistic regression model were developed to estimate the scores of the new score, designated as modified STESS (mSTESS), and it was subsequently compared with the STESS. Results: In all, 136 patients were included. Mean age was 62.01 ± 17.62 (19–95) years, and 54% were male. The capacity of the STESS to predict mortality was 74.3% (95% confidence interval 63.8%–81.8%), whilst the capacity of the mRS to predict mortality was 65.2% (95% confidence interval 54.2%–76.2%). The logistic regression model and receiver operating characteristic curves enabled the classification of mRS as follows: 0, mRS = 0; 1, mRS = 1–3; and 2, mRS > 3. These values, when added to the other items of the STESS, resulted in the mSTESS with scores between 0 and 8 points. The capacity of the mSTESS to predict mortality was 80.1%. An mSTESS > 4 established an overall accuracy of 81.8% for predicting mortality, which was considerably higher than the overall accuracy of STESS ≥ 3 (59.6%). Conclusions: The baseline mRS was associated with high mortality risk. It is proposed to use mSTESS to improve the prediction of mortality risk in SE.